Study of comparison of high resolution sonography and computed tomography in evaluation of abdominal tuberculosis among patients in Lucknow, Uttar Pradesh, India - Husain, Ayanat; Firdaus, Huma; Pandey, Piyush (International Surgery Journal, 2018)
Background: Despite individual evaluation of USG and CT scan in diagnosis of abdominal tuberculosis, there is limited literature available comparing the two methods. The present study was done to evaluate high resolution sonography and computed tomography in abdominal tuberculosis. Methods: A total of 55 clinically suspected adult cases of abdominal tuberculosis were enrolled in this prospective observational study after taking informed consent in a tertiary hospital of Lucknow. SPSS software version 15.0 statistical analysis software was used for data analysis. Results: The prevalence of abdominal tuberculosis among clinically suspected cases of abdominal tuberculosis was 77.8%. High resolution USG was 77.8% sensitive and 70% specific in diagnosis of abdominal tuberculosis. It provided a high efficacy in detection of intestinal tuberculosis but failed to provide a significant discriminatory difference between abdominal tuberculosis positive and negative cases for extra intestinal tuberculosis. Computed tomography was 35.3% sensitive and 80% specific in diagnosis of abdominal tuberculosis. It provided an excellent accuracy in diagnosing intestinal tuberculosis as well as extra-intestinal tuberculosis. The accuracy level of CT (90.9%) was found to be higher as compared to that of HR-USG (76.4%) and the difference was significant statistically too (p=0.039). Conclusions: Computed tomography is useful in diagnosis of both intestinal and extra-intestinal abdominal tuberculosis and can be recommended for use in routine practice.